2015
DOI: 10.1021/am508469h
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/Nanohydroxyapatite Scaffolds with Designed Core/Shell Structures Fabricated by 3D Plotting and in Situ Mineralization for Bone Tissue Engineering

Abstract: Composite scaffolds, especially polymer/hydroxyapatite (HAP) composite scaffolds with predesigned structures, are promising materials for bone tissue engineering. Various methods including direct mixing of HAP powder with polymers or incubating polymer scaffolds in simulated body fluid for preparing polymer/HAP composite scaffolds are either uncontrolled or require long times of incubation. In this work, alginate/nano-HAP composite scaffolds with designed pore parameters and core/shell structures were fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 54 publications
0
94
0
1
Order By: Relevance
“…[30][31][32][33] Based on that work, the aim of the present study was to develop novel high concentration plotting materials on the basis of gelatin and alginate for scaffold fabrication. [30][31][32][33] Based on that work, the aim of the present study was to develop novel high concentration plotting materials on the basis of gelatin and alginate for scaffold fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Based on that work, the aim of the present study was to develop novel high concentration plotting materials on the basis of gelatin and alginate for scaffold fabrication. [30][31][32][33] Based on that work, the aim of the present study was to develop novel high concentration plotting materials on the basis of gelatin and alginate for scaffold fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Alginate (Alg), an anionic linear polysaccharide consisting of 1,4-linked β-D-mannuronic acid (M) and α-Lguluronic acid (G) residues, [7][8][9] has been considered as a promising porous scaffold material because of its good biocompatibility, biodegradability, nontoxicity, and nonimmunogenicity. [14][15][16] However, properties to support the bone repair, maintain the stable structure, and provide suitable microstress environment for osteoblasts; (3) suitable biodegradation cycles to match the cell and tissue growth rate without toxic degradation products; (4) good affinity for the scaffolds to the surrounding tissues; and (5) good bone conductivity and osteoinductivity as a template for osteoblasts to grow, proliferate, differentiate, and speed up the repair of defective bone tissue. [14][15][16] However, properties to support the bone repair, maintain the stable structure, and provide suitable microstress environment for osteoblasts; (3) suitable biodegradation cycles to match the cell and tissue growth rate without toxic degradation products; (4) good affinity for the scaffolds to the surrounding tissues; and (5) good bone conductivity and osteoinductivity as a template for osteoblasts to grow, proliferate, differentiate, and speed up the repair of defective bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated that HA exhibits poor mechanical properties, including high brittleness and low elasticity thus limiting its application directly as a bone substitute in the bone tissue engineering (9, 10). In view of this, synthesis and characterization of nano sized HA have received intensive interest in nanoscience and nanotechnology (11, 12). However, it needs a supportive biodegradable skeleton such as polycaprolactone (PCL) fibers.…”
Section: Introductionmentioning
confidence: 99%